Pengaruh Promosi Penjualan dan Motivasi Belanja Hedonis terhadap Pembelian Impulsif pada Aplikasi Shopee - Kartika Sukmawati (Trending: Jurnal Manajemen dan Ekonomi, 2024)
In the modern era, the development of technology, information and communication is progressing very rapidly. Almost all activities are influenced by internet use, especially in the economic and business fields. The level of internet users and high public interest in the convenience of online shopping make Indonesia a promising market share for e-commerce. Shopee is an e-commerce that can attract consumers so that they can carry out buying and selling transactions online. This research aims to determine the effect of sales promotions and hedonic shopping motivation on impulse purchases on the Shopee application. This research method uses primary data with a quantitative approach and the tests carried out are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis Test, Hypothesis Test including T Test (Partial) and F Test (Simultaneous) and Coefficient of Determination Test ( R2). By distributing online questionnaires via Google Form, 100 respondents were collected and provided valid data for this research. In this research, the sampling method is nonprobability sampling with purposive sampling technique. The tool for testing in this research is SPSS V25. The results of this research show that the Sales Promotion and Hedonic Shopping Motivation variables, both partially and simultaneously, have a significant effect on Impulsive Buying on the Shopee Application.